Proceedings of the 15th International Conference on Mining Software Repositories 2018
DOI: 10.1145/3196398.3196401
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of security vulnerabilities in the npm package dependency network

Abstract: Security vulnerabilities are among the most pressing problems in open source software package libraries. It may take a long time to discover and fix vulnerabilities in packages. In addition, vulnerabilities may propagate to dependent packages, making them vulnerable too. This paper presents an empirical study of nearly 400 security reports over a 6-year period in the npm dependency network containing over 610k JavaScript packages. Taking into account the severity of vulnerabilities, we analyse how and when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 22 publications
4
121
0
1
Order By: Relevance
“…Derr et al [24] conducted a survey with more than 200 mobile app developers in the Android ecosystem to investigate the use of outdated libraries, and reported that almost 98% of 17K actively used library versions with a known security vulnerability could be easily fixed by updating the library. Decan et al [25] empirically studied nearly 400 security reports for 269 npm packages, and found that more than 40% of the releases depending on a vulnerable package do not automatically benefit from the security fixes because of too restrictive dependency constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Derr et al [24] conducted a survey with more than 200 mobile app developers in the Android ecosystem to investigate the use of outdated libraries, and reported that almost 98% of 17K actively used library versions with a known security vulnerability could be easily fixed by updating the library. Decan et al [25] empirically studied nearly 400 security reports for 269 npm packages, and found that more than 40% of the releases depending on a vulnerable package do not automatically benefit from the security fixes because of too restrictive dependency constraints.…”
Section: Related Workmentioning
confidence: 99%
“…They found that “the time lag behind the newest release of a library is measured in the order of years,” and that this is a major source of known vulnerabilities in websites using these libraries. They also observed that “libraries included transitively [...] are more likely to be vulnerable.” Decan et al carried out an empirical analysis of security vulnerabilities in the npm repository by analyzing how and when these vulnerabilities are discovered and fixed, and to which extent they affect other package releases in the repository in presence of dependency constraints. They observed that it often takes a long time to discover vulnerabilities since their introduction.…”
Section: Related Workmentioning
confidence: 99%
“…Since our RQ3 is asking the same questions as our RQ1 and RQ2, but with a different condition, we present the answer of RQ3 together with the answers of RQ1 and RQ2. 12 https://greenkeeper.io/…”
Section: Resultsmentioning
confidence: 99%
“…The NPM ecosystem is one of the most active and dynamic JavaScript ecosystems and [31] presents its dependency structure and package popularity. Studies on NPM have mostly focused on its dependency networks [12], its effect on popularity of NPM packages [13], and problems associated with library migration [33].…”
Section: Related Workmentioning
confidence: 99%